Juvenile granulosa cell tumor presenting as isosexual precocious puberty: A case report and review of literature - Nisha Nigil Haroon; Gaurav Agarwal; Rakesh Pandey; Preeti Dabadghao (Indian Journal of Endocrinology and Metabolism, 2013)
The differential diagnosis for precocious puberty in a young female includes peripheral causes. This case report documents a rare cause of isosexual precocious puberty, a juvenile granulosa cell tumor of the ovary-and a brief literature review. A 7-year-old girl presented with rapid onset of pubertal development and elevated estradiol levels. Abdominal ultrasound revealed a mass in the right adnexa. Other causes of precocious puberty were excluded. Elective surgery was planned, but the patient presented to the emergency room with torsion of ovary. She underwent an exploratory laparotomy for tumor resection and right salpingo oophorectomy. Pathology reported a juvenile granulosa cell tumor of the ovary. Postoperatively, she experienced a cessation of vaginal bleeding and estradiol levels normalized. Early stage disease has good prognosis. Adjuvant chemotherapy is not indicated in this setting.